Design and test of one-rotor orchard horizontal rotary rake based on tine movement trajectory analysis - Lei, Xiaohui; Lyu, Xiaolan; Shen, Yongzhe; Qian, Shicheng; Zeng, Jin; Yuan, Quanchun; Qi, Yannan; Huang, Wanxi; Ma, Zhengbao (International Journal of Agricultural and Biological Engineering, 2025)
To solve the problem of effective utilization of orchard green fertilizer, a small one-rotor orchard horizontal rotary rake (OHRR) was developed, which is used for grass collection in the mowing agronomic section of orchard management. In the working process, the disc drives the arms rotating around the vertical shaft, the guide cam that is fixed to the vertical shaft controls tine movement, and the tines turn to different inclination angles in different positions. The kinematic validation model of OHRR was built based on the theory that there is no gap or small overlap between the two adjacent working areas of the tines. This model determines the relationship between the advancing speed, disc rotational speed, rotation radius, arm number, and tine working width. The leakage and repeating rate of OHRR virtual prototype were calculated by tines movement trajectories analysis in multi-body dynamics simulation. Box-Behnken three-factor and three-level test plans for advancing speed, disc rotational speed, and tine working width were designed to obtain the optimal operation parameters of the OHRR: advancing speed was 11.16 km/h, disc rotational speed was 6.98 rad/s, and tines working width was 0.3 m. Taking labor working as the control group, OHRR field tests were evaluated by four indices: strip density, leakage rate, working efficiency, and profitable area. Field tests results showed that the leakage rate of OHRR was 4.56%, which meets the requirements of national standard JB/T10905. The strip density, width, and height of OHRR were 29.44 kg/m3, 0.5 m, and 0.25 m, respectively. These data can provide support for the subsequent loading and transportation operation. The profitable area of OHRR was 6.7 hm2, which is suitable for large-scale mechanized orchard management. Key words: orchard; rake; tine movement model; performance parameter; trajectory optimizationDOI: 10.25165/j.ijabe.20251802.9194Citation: Lei X H, Lyu X L, Shen Y Z, Qian S C, Zeng J, Yuan Q C, et al. Design and test of one-rotor orchard horizontal rotaryrake based on tine movement trajectory analysis. Int J Agric & Biol Eng, 2025; 18(2): 115–123.